Comparison between qualitative and quantitative measurement of strength deficit in shoulder flexors of young females: a cross- sectional study - Perwaiz, Saadia; Afzal, Muhammad Waqar; Fatima, Ghulam (Journal of the Pakistan Medical Association, 2021)
Objective: To compare accuracy of manual muscle testing in detection of strength differences across grade 4 and 5 at different percentage deficits of dynamometric mean in shoulder flexors of young females. Methods: Cross sectional research design, conducting primary analysis of strength of shoulder flexors measured through manual muscle testing and hand-held dynamometer. Three hundred young healthy females without any ailment of upper extremity or generalized health problem were selected from University of South Asia and Association of Fatima Jinnah Old Graduates, Lahore. Non-probability convenient sampling technique was used. The age group selected was 18-39 years. The strength of shoulder flexors measured through manual muscle testing and hand-held dynamometer was main outcome measure. Results: The overall diagnostic accuracy of manual muscle testing showed better results at 10% dynamometric measures. It was 63.33%(95% CI: 57.74%, 68.59%) in non-dominant shoulder flexors and 61.67% (95% CI: 56.05%, 66.99%) in dominant shoulder flexors. The positive predictive value (PPV) and specificity of manual muscle testing was better at 10% strength deficit in comparison with dynamometric measures, whereas negative predictive value (NPV) and sensitivity was better at 20% strength deficit. Contrasting association was found between positive predictive value (PPV) and sensitivity, negative predictive value and specificity. Conclusion: The subjective area of grade 4 and 5 showed better, although not ideal, diagnostic worth at 10% deficit of dynamometric measures in shoulder flexors. Further exploration through study of contrasting trends between PPV and sensitivity by subgroup analysis is required. Continuous...